(untitled) (Al-Farooq Journal of Sciences, 2026)
This study analyzes Mark Zuckerberg’s educational speech through the framework of Gee’s Seven Building Tasks of language. The aim of this study is to discuss how language is used to construct meaning, ideas of learning, success, knowledge, and personal development in Zuckerberg’s speech. The study uses qualitative approach and applies spoken discourse analysis to the chosen speech. The data of this study are taken from the transcript of Zuckerberg’s 2017 Harvard Commencement speech analyzed by using Gee’s Seven Building Tasks: Significance, Activities, Identities, Relationship, Politics, Connections, and Sign System Knowledge. The study examines particular words, expressions, and rhetorical strategies that shape audience’s understanding of learning and success. Through this framework we can see that language plays an important role in building educational messages and social values in public speeches. This research provides a better understanding of how educational discourse shapes the idea of learning and success. It contributes to discourse analysis by showing that Gee’s framework is useful for studying spoken educational texts and uncovering the ideologies and meanings expressed through the language.